CORRECTION OF METABOLIC DISORDERS IN THE TREATMENT AND PROPHYLAXIS OF PATIENTS WITH INSULIN-DEPENDENT DIABETES MELLITUS - Zavgorodnaya, N.G.; Mikhalchik, S.V. (World of Medicine and Biology, 2017)
In recent years, virtually all countries have experienced a steady increase in the incidence of diabetes mellitus. The purpose of this work is to increase the efficiency of treatment of patients with non-proliferative DR (CDR) by including short carotenoids in the complex therapy of patients. 94 patients with type 2 diabetes with diabetic retinopathy were examined. Based on the revealed AFC-dependent mechanisms of the formation of diabetic retinopathy, the expediency of inclusion in the complex therapy of diabetic retinopathy of short-chain carotenoid - Multicarinol in order to correct the expression of molecular factors of angiogenesis, nitroxidergic system and increase of visual functions has been substantiated and proved. Based on the revealed AFK-dependent mechanisms of the formation of diabetic retinopathy, it was reasonably proved and expedient to include in the complex therapy of diabetic retinopathy a short-chain carotenoid -Multicarinol with the aim of correcting the expression of molecular factors of angiogenesis, the nitroxydergic system and enhancing visual functions. Course adjournment of antioxidants on the example of carotenoids led to an increase in ophthalmic functions in varying degrees of severity, the normalization nitroxidergic system, and inhibition of nitroziruyuschego stress, manifested in reducing the activity of NOS, a decrease in hyperproduction of NO and nitrotyrosine - these data are the basis for the use of short antioxidants carotenoids as neuroprotectors in complex therapy and prevention of diabetic angiotensinopathy.
Keywords: nonproliferative diabetic retinopathy; short carotenoids; treatment diabetes mellitus